EMOTION ESTIMATION THROUGH 3D CONVOLUTIONAL NEURAL NETWORK IN VIDEOS - Rakhimzhanova, Jamilya (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The project aims to present the methods of emotion estimation with a use of convolutional neural networks (3DCNN). Recognizing human emotions allow us to create user friendly devices and allow for devices to respond effectively to user needs. One potential application is in the healthcare field. Tools with effective emotion recognition algorithms can be used to treat and diagnose patients with mental health conditions, such as anxiety or depression. In marketing, these tools can be used to adjust preferences to consumer wants as currently done by AI tools.
Keywords: Type of access: Restricted; Emotion Recognition